Nematoda Parasit Pada Bunomys spp. di Pegunungan Mekongga, Sulawesi Tenggara - Muhammad Falikhul Musyaffa'; Kartika Dewi; Mochammad Irfan Hadi (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2021)
Study on the nematode parasite species of Bunomys spp. from Mekongga Mountain, Southeast Sulawesi was conducted on deposited specimens in Museum Zoologicum Bogoriense, Zoology Division, Research Center of Biology-LIPI. Bunomys is endemic genus murine rodent in Sulawesi. This study aims to determine the types of nematodes in endemic Muridae rodent, the results of which can help the government in developing disease management plans. The nematodes identified in this study were Subulura andersoni (host: B. andrewsi), Syphacia rifaii (host: B. chrysocomus), Cyclodostomum purvisi (host: B. penitus), Heterakis spumosa (host: B. chrysocomus). Except for Sy. muris, all of the recorded nematodes have worldwide distribution. Morphology and taxonomy of nematodes will be discussed in this paper